2017
DOI: 10.1002/cpp.2117
|View full text |Cite
|
Sign up to set email alerts
|

Preschool children's response to behavioural parent training and parental predictors of outcome in routine clinical care

Abstract: BPT under routine care conditions clearly improves disruptive behaviours in preschool children. Mothers who consider themselves as inadequate in disciplining and mothers whose partners do not consume high levels of alcohol report the largest improvements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 39 publications
1
9
0
1
Order By: Relevance
“…Although one of the secondary caretakers was a grandmother, we report on secondary caretakers as “fathers”. Compared to the sample analyzed in our previous study (Van der Veen‐Mulders et al, ), we could not analyze data of five families because they failed to provide T2 ratings.…”
Section: Methodssupporting
confidence: 91%
See 2 more Smart Citations
“…Although one of the secondary caretakers was a grandmother, we report on secondary caretakers as “fathers”. Compared to the sample analyzed in our previous study (Van der Veen‐Mulders et al, ), we could not analyze data of five families because they failed to provide T2 ratings.…”
Section: Methodssupporting
confidence: 91%
“…As expected, and also in line with previous studies (Ghuman et al, ), we found both fathers and mothers in the clinical sample reporting more inadequate parenting skills and lower parenting sense of competence before parent training than parents of children in the nonclinical sample. In a previous paper we had already reported that our behavioural parent training decreased disruptive behaviours (Van der Veen‐Mulders et al, ).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Although the emotional consequences of homicidal loss evidently merit clinical attention, options for preventive and curative treatments are scarce. In existing literature on the treatment of traumatic loss, grief- and trauma-focused interventions are described, as well as interventions integrating working mechanisms of both ( 23 , 24 ). For the treatment of PTSD, trauma-focused cognitive behavioral therapy (CBT) and Eye Movement Desensitization and Reprocessing (EMDR) are implemented in treatment guidelines ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…Initial trials of CSE showed broad support for reducing overall symptom severity, and to some degree voices ( Tarrier et al, 1993a , Tarrier et al, 1993b ). More recently, the approach has been confirmed as feasible as a four-session model specifically targeting voices ( Hayward et al, 2018 ; Paulik et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%